Paediatric lumbar punctures: How do paediatric and emergency doctors differ?. (9th April 2017) - Yeong, Chee Cheen; Craig, Simon S; Cheek, John A
Abstract: Objective: The objective of the study was to identify any differences between emergency physicians and emergency trainees and paediatricians and paediatric trainees in performing paediatric lumbar punctures (LPs). Methods: Anonymous cross‐sectional electronic survey was distributed to emergency physicians, emergency trainees, paediatricians and paediatric trainees within three hospitals of a single public health network. There were four standardised clinical scenarios (neonate, infant, young child and adolescent), with accompanying questions relating to neurological evaluation and imaging prior to LP, the use of written consent forms and parental presence during the procedure. Results: Paediatricians and paediatric trainees have greater confidence performing LP on neonates and infants, while emergency physicians and emergency trainees are more confident in older children. The only differences in self‐reported neurological examination prior to LP was paediatricians and paediatric trainees being more likely to perform fundoscopy than were emergency physicians and emergency trainees in infants (21% vs 8%, P  = 0.03) and young children (44% vs 16%, P  < 0.001). Less than half of both groups of doctors would obtain written consent for paediatric LPs. Emergency physicians and emergency trainees were much more likely to encourage parents to remain in the room during the procedure than their paediatric counterparts (95% vs 37%, P  < 0.0001). Conclusion: Paediatricians and paediatric trainees are more likely to be confident in performing LP in very young children than are emergency physicians and emergency trainees. They are more likely to perform fundoscopy prior to the procedure, but are much less likely to encourage parental presence during the LP.